Peran Kepala Sekolah dalam Meningkatkan Motivasi Guru untuk Menggunakan E-Learning pada Masa Covid 19 Jurusan Teknik Komputer di Sekolah Menengah Kejuruan Negeri 2 Palopo - Hilal Mahmud; Munir Yusuf; Lilis Purnanengsi Mas’ud (Fakultas Tarbiyah dan Ilmu Keguruan, 2020)
Abstract[English]:This study aims to determine the principal's efforts in increasing teacher motivation to use e-learning during the covid 19 period, majoring in computer engineering at SMK Negeri 2 Palopo and to determine the work motivation of teachers to use e-learning during the covid 19 period. Computer Engineering Department at SMK Negeri 2 Palopo. This type of research is descriptive qualitative, using a pedagogical and educational approach. The results of the research researchers are as follows. 1) the principal's efforts to increase teacher motivation to use e-learning, namely; motivation, directing and guiding teachers to participate in training related to e-learning, complementing the needs of teachers both in terms of facilities and infrastructure and developing the work of teachers. 2) teacher's work motivation to use e-learning, where teachers are able to increase work motivation in carrying out learning tasks by making easy learning models so that they are able to solve the level of difficulty experienced by participants during e-learning learning and teachers and school principals work together and support each other to improve teacher competence in carrying out e-learning learning activities.Abstrak[Indonesia]:Penelitian ini bertujuan untuk mengetahui upaya kepala sekolah dalam meningkatkan motivasi guru untuk menggunakan e-learning pada masa covid 19 jurusan teknik komputer di SMK Negeri 2 Palopo dan untuk mengetahui motivasi kerja guru untuk menggunakan e-learning pada masa covid 19 Jurusan Teknik Komputer di SMK Negeri 2 Palopo. Jenis penelitian ini adalah deskripsif kualitatif, dengan menggunakan pendekatan pedagogis dan edukatif. Hasil penelitian peneliti sebagai berikut. 1) upaya kepala sekolah dalam meningkatkan motivasi guru untuk menggunakan e-learning yakni; memberikan dorongan motivasi, mengarahkan dan membimbing guru untuk mengikuti kegiatan pelatihan yang berkaitan dengan pembelajaran e-learning, melengkapi kebutuhan guru baik sarana dan prasarana dan mengevaluasi hasil kerja guru. 2) motivasi kerja guru untuk menggunakan e-learning, dimana guru mampu meningkatkan motivasi kerja dalam menjalankan tugas pembelajaran dengan cara membuat model pembelajaran yang mudah sehingga mampu menyelesaikan tingkat kesulitan yang dialami peserta didik selama pembelajaran e-learning serta guru dan kepala sekolah berkerjasama dan saling mendukung untuk meningkatkan kompotensi guru dalam melaksanakan kegiatan pembelajaran e-learning.